Renal denervation Really an alternative to reducing blood pressure? - Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (Internist, 2022)
Since the current guidelines were published in 2018, a total of 5 sham-controlled high-quality studies evaluating renal denervation have been conducted and the results were published. These five studies clearly confirmed the efficacy and safety of renal denervation, which correspond to the knowledge of the Clinical Consensus Conference. Thus, an update of the guidelines for the treatment of arterial hypertension regarding the clinical significance of renal denervation is urgently necessary. For this reason, the position paper of the working group of the European Society of Hypertension on the current state of renal denervation was reviewed. An approval of this procedure can soon be expected. In Germany there is a diagnosis-related group (DRG) for the reimbursement of renal denervation, which was suspended due to the erroneous Symplicity 3 study. This DRG should be revived in practice by a structured process of the implementation of renal denervation. It will then be a joint task of treating physicians and specialists in certified centers to identify eligible patients. In the future, antihypertensive treatment will consist of three pillars: lifestyle measures, pharmacotherapy and interventional treatment. These three treatment options should not be regarded as competitive (which is better) but alternative (patient preference) and additive (the aim is blood pressure control). It is the task of the treating physician to provide the patient with the ideal treatment concept. Clearly, renal denervation will not replace antihypertensive pharmacotherapy; however, it can lead to a reduction of the drug burden and increase of patient adherence to medication. It represents an option of modern antihypertensive treatment and will also become increasingly more important in special patient groups.
CRIS-Team WoS Importer:2022-01-21